2019
DOI: 10.3390/ijms20215286
|View full text |Cite
|
Sign up to set email alerts
|

The Modulating Effect of p-Coumaric Acid on The Surface Charge Density of Human Glioblastoma Cell Membranes

Abstract: p-Coumaric acid (p-CoA), a phenolic acid belonging to the hydroxycinnamic acids family, is a compound with tentative anticancer potential. Microelectrophoretic mobility measurements conducted at various pH values of electrolyte solution were applied to study p-CoA effects on electrical properties of human glioblastoma cell membranes. The obtained results demonstrated that after the p-CoA treatment, the surface charge density of cancer cells changed in alkaline pH solutions, while no noticeable changes were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…LN-229 cells treated with either CA or FA showed an increase in positive charge at low pH and a decrease in negative charge at high pH in comparison to untreated cells. These results seem to be in agreement with other reports demonstrating similar tendency for various cancer cell membranes treated with chemotherapeutic agents [ 18 , 57 , 58 ]. It has already been well documented that polyphenols exhibit affinity for the lipid bilayer by binding to the lipid head groups near the bilayer surface (adsorption) and penetration into the bilayer interface (absorption).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…LN-229 cells treated with either CA or FA showed an increase in positive charge at low pH and a decrease in negative charge at high pH in comparison to untreated cells. These results seem to be in agreement with other reports demonstrating similar tendency for various cancer cell membranes treated with chemotherapeutic agents [ 18 , 57 , 58 ]. It has already been well documented that polyphenols exhibit affinity for the lipid bilayer by binding to the lipid head groups near the bilayer surface (adsorption) and penetration into the bilayer interface (absorption).…”
Section: Discussionsupporting
confidence: 93%
“…One of the techniques that might be used to estimate zeta potential is the electrophoretic light scattering (ELS) technique based on dynamic light scattering (DLS), in which the shift in the frequency or in the oscillation phase of the laser beam depends on the mobility of particles/cells in an alternating electric field [ 14 ]. In this respect, in our previous works, we have already applied the ELS technique to study human glioblastoma cells treated with either silica nanoparticles [ 14 , 15 ] or phenolic compounds such as quercitin [ 16 ] and p-coumaric acid [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The location and permeability of polyphenols through membranes depends on the pH and charge. For example, using model lipid membranes, it was shown that at a lower pH, p -coumaric acid has a lower deprotonation state and penetrates deeper into the cell, so this is a feature conditioning its biological efficiency [ 218 ].…”
Section: Structure Elements and Biological Activitymentioning
confidence: 99%
“…In line with previous reports, many of these compounds may act as chemopreventive or even chemotherapeutic agents [ 5 , 7 , 8 , 9 ]. Specifically to malignant cells, cinnamic acid (CinA) and its hydroxy derivatives have been shown to exhibit both antioxidant a antineoplastic activity, with their cytostatic effect being largely related to their structural characteristics [ 10 , 11 , 12 , 13 ]. However, the mode of action of CinA and its derivatives is still incompletely determined, but may involve scavenging of reactive oxygen species, modulation of gene expression, activation of xenobiotics metabolism-related enzymes, and regulation of signal transduction pathways essential for tumor cell growth and progression [ 14 ].…”
Section: Introductionmentioning
confidence: 99%